XRISM Constrains Atmospheric Motion and Turbulent Dissipation in the Archetypal Radio-mode Feedback System Hydra-A - Tom Rose; B. R. McNamara; Julian Meunier; A. C. Fabian; Helen Russell; Paul Nulsen; Neo Dizdar; Timothy M. Heckman; Michael McDonald; Maxim Markevitch; Frits Paerels; Aurora Simionescu; et al. (The Astrophysical Journal)
We present XRISM Resolve observations centered on Hydra-A, a redshift z = 0.054 brightest cluster galaxy, which hosts one of the largest and most powerful FR-I radio sources in the nearby Universe. We examine the effects of its high jet power on the velocity structure of the cluster’s hot atmosphere. Hydra-A’s central radio jets have inflated X-ray cavities with energies upward of 10 ^61 erg. They reach altitudes of 225 kpc from the cluster center, well beyond the atmosphere’s central cooling region. Resolve’s 3′× 3′ field of view covers 190 × 190 kpc, which encompasses most of the cooling volume. We find a one-dimensional atmospheric velocity dispersion across the volume of 164 ± 10 km s ^−1 . The fraction in isotropic turbulence or unresolved bulk velocity is unknown. Assuming pure isotropic turbulence, the turbulent kinetic energy is 2.5% of the thermal energy radiated away over the cooling timescale, implying that kinetic energy must be supplied continually to offset cooling. While Hydra-A’s radio jets are powerful enough to supply kinetic energy to the atmosphere at the observed level, turbulent dissipation alone would struggle to offset cooling throughout the cooling volume. The central galaxy’s radial velocity is similar to the atmospheric velocity, with an offset of −37 ± 23 km s ^−1 .